2011
DOI: 10.1097/aln.0b013e3182084a70
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Neuroapoptotic Properties of Equipotent Anesthetic Concentrations of Desflurane, Isoflurane, or Sevoflurane in Neonatal Mice

Abstract: In neonatal mice, equipotent doses of the three commonly used inhaled anesthetics demonstrated similar neurotoxic profiles, suggesting that developmental neurotoxicity is a common feature of all three drugs and cannot be avoided by switching to newer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(170 citation statements)
references
References 59 publications
6
160
2
2
Order By: Relevance
“…In fact, blockade of NMDA receptors with MK801 resulted in widespread apoptosis in the brains of 7-day-old rats [3]. Subsequently, many other studies demonstrated accelerated neuronal apoptosis in newborn rodents after they were exposed only to general anaesthetics such as ketamine, propofol, nitrous oxide, sevoflurane, isoflurane, desflurane, and benzodiazepines, without any other insults [2,[4][5][6][7][8][9][10]. In rats, the effect of anesthetics on apoptosis was greatest in 5-7 day olds.…”
Section: Effects Seen In Animal Studiesmentioning
confidence: 99%
“…In fact, blockade of NMDA receptors with MK801 resulted in widespread apoptosis in the brains of 7-day-old rats [3]. Subsequently, many other studies demonstrated accelerated neuronal apoptosis in newborn rodents after they were exposed only to general anaesthetics such as ketamine, propofol, nitrous oxide, sevoflurane, isoflurane, desflurane, and benzodiazepines, without any other insults [2,[4][5][6][7][8][9][10]. In rats, the effect of anesthetics on apoptosis was greatest in 5-7 day olds.…”
Section: Effects Seen In Animal Studiesmentioning
confidence: 99%
“…Caspase-3 serves a vital role in the apoptotic pathway (41), and in previous studies, cleaved caspase-3 expression levels were used as a marker of apoptotic cell death (2,4,5,33). Rutin effectively downregulated the expression levels of activated caspase-3, in addition to the apoptotic cell count.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential detrimental effects of anesthetic exposure to neonatal animals in terms of causing neurohistopathological changes and long-term behavior deficits and cognitive dysfunctions (6,32,33). Apoptotic cell death is an essential part of normal brain development and maturation, leading to the elimination of ~50-70% of neurons and progenitor cells during the development of the central nervous system (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been observed to occur acutely in the period immediately following anesthesia (Jevtovic-Todorovic et al, 2003;Istaphanous et al, 2011;Shih et al, 2012), and the thalamus and hippocampus are known areas susceptible to extensive neurodegeneration (JevtovicTodorovic et al, 2003;Satomoto et al, 2009;Shih et al, 2012). …”
Section: Introductionmentioning
confidence: 99%